Multilevel Intervention Program Goes to School Camba' Rokok for School Based Smoking Prevention - Indra Amanah; Ishak (Universitas Airlangga, 2024)
Background: The earlier age people start smoking will have the potential to become long-term smokers. One way that can be done to overcome this problem is through program intervention such as a promotive preventive program that is focused on addressing the problem of smoking is urgently needed. In the City of Palopoin 2017 smokers of elementary school children reached 15.27%, people who broke the rules by smoking in schools reached 44.27% and 36.64% of students had been exposed to outdoor cigarette advertisements. Aims: This study aims to assess the program Goes to school camba' rokok in multilevel interventions at the student and school level to increase self-efficacy and skills in school-based smoking prevention. Methods: The population in this study was state junior high school and senior high school in Palopo city. This research is a quasi-experimental study, with a Solomon four-group design. The samples in this study were 131 students who were randomly determined at SMAN 2 Palopo, SMAN 4 Palopo, SMPN 5 Palopo, and SMPN 8 Palopo using simple cluster random sampling tests. Data analysis using STATA for statistical analysis using statistical tests with Wilcoxon, Mann-Whitney, and Kruskal-Wallis at the significance level p-value <0.05. Results: Posttest scores in the four groups, there was a significant difference in the effect of program interventions going to school camba' rokok on self-efficacy with a p-value of 0.0001, skills with a p-value of 0.0012. Conclusion: There is an increase in students 'self-efficacy and skills through a multilevel intervention program going to school camba' rokok in Palopo City.